Massive Hemoptysis in Children - Juan Yang; Fengqin Liu; Yan Liang; Chunyan Guo; Jinrong Wang; Xing Chen (Canadian Respiratory Journal)
Rationale. Hemoptysis is a rare but often life-threatening condition in pediatric patients. Massive hemoptysis can easily lead to asphyxia, respiratory failure, shock, and even death. The most common causes of severe hemoptysis are lower respiratory tract infection, vascular malformation, and bronchial foreign body. We present an unusual case of massive hemoptysis caused by malformation of the bronchial artery, which includes bronchial artery hypertrophy, bronchial-pulmonary artery fistula, and ectopic bronchial artery. Patient. An 11-year-old boy was admitted to the hospital with mild hemoptysis lasting for the two preceding days. He did not report any discomfort, such as fever or chest pain. His complete blood count and coagulation function were normal. Chest X-ray documented lower right pneumonia. Massive hemoptysis occurred on the night of the admission. Diagnosis. Bronchial arteriography revealed that the right lower bronchial artery and the ectopic bronchial artery from the renal artery were the responsible vessels for hemoptysis. Interventions. The boy underwent a successful bronchial artery embolization and bronchoscopy to remove the blood clot from the airway. Outcomes. After bronchial artery embolization and bronchoscopy, the boy recovered without complications. Hemoptysis and chest pain disappeared, and chest radiographs returned to normal. Lessons. Bronchial arterial bleeding often presents as life-threatening massive hemoptysis. Patients should immediately receive hemostatic treatment and undergo chest CTA, bronchial arteriography, BAE, and bronchoscopy according to their condition. Rapid identification of the etiology and symptomatic treatment are critical to saving the lives of children.